Effect of Sn Incorporation on Physical Parameters of Sb-Se Glassy System - Khajuria, R.; Sharma, A.; Sharma, P. (Journal of Scientific Research, 2020)
The rationale of this study is to investigate band gap tailoring of Sb-Se-Sn chalcogenide glasses. This study has been accompanied by the assessment of various theoretical parameters such as average co-ordination number, Lone-pair of electrons, number of constraints, average heat of atomization, mean bond energy and glass transition temperature. It has been observed that almost all these physical parameters have been enhanced with the increase in tin (Sn) content except Lone-pair of electrons. The number of lone-pair electrons has been decreased with the increase in Sn content. The glass transition temperature has been observed to increase due to the addition of Sn atom in the Se-Sb glassy system. The band gap is decreasing with increase in Sn content due to overall decrease in the average single bond energy of the Sb-Se-Sn glassy system.